2012
DOI: 10.14221/ajte.2012v37n8.2
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking Sport Teaching in Physical Education: A Case Study of Research Based Innovation in Teacher Education

Abstract: This paper focuses on the significance of physical education teacher education (PETE) (Drummond & Pill, 2011;Pill, 2009Pill, , 2010

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0
16

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(57 citation statements)
references
References 59 publications
(45 reference statements)
1
34
0
16
Order By: Relevance
“…It has been regularly reported that PE experiences developed via an 'apprenticeship of observation' from primary and secondary schooling can have a major impact on PSTs (Jenkins, Garn, & Jenkins, 2005;Pill, Penney, & Swabey, 2012;Wrench & Garrett, 2012;Hyndman, 2014;Hyndman & Pill, 2016) and can be firmly stored in memory (Humphries & Ashy, 2006). The nature of future PE provision will "depend on the insights and commitments of the professionals responsible for future curriculum decisions" (Wiegand, Bulger, & Mohr, 2004, p.7).…”
Section: The Educative Implications Of Gaining Social-ecological Insimentioning
confidence: 99%
See 1 more Smart Citation
“…It has been regularly reported that PE experiences developed via an 'apprenticeship of observation' from primary and secondary schooling can have a major impact on PSTs (Jenkins, Garn, & Jenkins, 2005;Pill, Penney, & Swabey, 2012;Wrench & Garrett, 2012;Hyndman, 2014;Hyndman & Pill, 2016) and can be firmly stored in memory (Humphries & Ashy, 2006). The nature of future PE provision will "depend on the insights and commitments of the professionals responsible for future curriculum decisions" (Wiegand, Bulger, & Mohr, 2004, p.7).…”
Section: The Educative Implications Of Gaining Social-ecological Insimentioning
confidence: 99%
“…The developmental overlay has been described as a "transformative process of forming socio-culturally responsive teacher professional identities" (Pill & Brown, 2007, p. 15). Teacher education programs have the potential to provide PSTs with opportunities to 'frame, disrupt and reframe' pre-existing PE perceptions (Pill et al, 2012). The SEM provides an effective model to understand that a transformative teaching process is possible if influences beyond an individual teacher's control are considered.…”
Section: The Educative Implications Of Gaining Social-ecological Insimentioning
confidence: 99%
“…Other research on English PETE stresses that PSTs and their mentors frequently continue to prioritise content knowledge over other knowledge bases and favour knowledge with direct practical application for the school setting during their teacher education (Kinchin, 2009). Capel et al (2011) observe that the pre-dominance of traditional sporting practices and content-centred approaches to teaching physical education in many English schools continues to present significant challenges to developing critically reflective, pupil-centred teaching practices through PETE, and is an issue of international concern (Pill, Penney and Swabey, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The PE teacher's role in the learning process becomes that of the facilitator and mediator (Dyson et al, 2004;Mitchell, Griffin, & Oslin, 2006;Pill, Penney, & Swabey, 2012). Thus, a more dialectical approach is adopted (Stolz & Pill, 2014) that utilizes pedagogically appropriate questions (Bell, 2003;Chatzipanteli & Digelidis, 2012;Griffin & Sheehy, 2004;McNeill, Fry, Wright, Tan, & Rossi, 2008;Mitchell et al, 2006) in an authentic learning environment related to real-game situations (Dyson et al, 2004;Pill et al, 2012).…”
Section: Pedagogical Models To Teaching Games In Physical Educationmentioning
confidence: 99%
“…Thus, a more dialectical approach is adopted (Stolz & Pill, 2014) that utilizes pedagogically appropriate questions (Bell, 2003;Chatzipanteli & Digelidis, 2012;Griffin & Sheehy, 2004;McNeill, Fry, Wright, Tan, & Rossi, 2008;Mitchell et al, 2006) in an authentic learning environment related to real-game situations (Dyson et al, 2004;Pill et al, 2012). Students are provided with opportunities to collaboratively investigate and solve tactical and strategic problems (Light, 2008) that facilitate the construction of their knowledge (Dyson et al, 2004).…”
Section: Pedagogical Models To Teaching Games In Physical Educationmentioning
confidence: 99%